Analysis of e-commerce strategies in the textile sector: Dimatex case - Laverde Yepes , Laura Natalia (2023)
The present investigation analyzes the different strategies of electronic commerce that can be implemented in the Dimatex company. The type of research had a qualitative approach, that is, information was collected on the textile sector and the importance of e-commerce through the years The method used was a case study, that is, the process by which the company Dimatex has passed in its years in the market was analyzed, and we also analyzed the benefits that the implementation of e-commerce could provide to the company; subsequently, different strategies and keys of e-commerce. The scope of this project is proactive and analytical, because with the information that was collected a specific proposal was made and why these strategies were sought by analyzing the different variables, looking for relate those strategies that best suit Dimatex. 8 e-commerce strategies in the textile sector were evidenced to carry out their activities, strategies such as website creation, use of SEM (search engine marketing), SEO (search engine optimization) and SMO (social media optimization) techniques, affiliate marketing, the constant use of social networks, e-mail marketing and finally the business blog. The result of the investigation allowed to identify that, for Dimatex, the right strategies to implement are the business blog, the creation of the website and the constant use of social networks.